Tantangan Digitalisasi dalam Pencatatan Biaya Proyek pada PT. Bangun Mitra Persada - Aini, Syarifah; Syaiful Akbar, Fajar (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to examine the various challenges encountered by PT. Bangun Mitra Persada in its efforts to digitize project cost recording processes. Despite handling large-scale construction projects worth billions, the company still relies on manual data entry through Microsoft Excel. Employing a qualitative case study approach, data were gathered through semi-structured interviews, limited field observations, and document analysis. The findings reveal three primary obstacles to digitalization: limited human resource capabilities, a perception that the current business scale does not justify digital systems, and the prevalence of inefficiencies and errors within the manual process. The research highlights that the barriers to digital adoption are not solely technical but also deeply rooted in organizational readiness and internal work culture. Conceptually, the study extends the application of the Technology Acceptance Model (TAM) and Organizational Readiness theory within the context of small to medium-sized enterprises (SMEs) in the construction sector. Practically, it provides actionable insights for system developers and policymakers in designing adaptive and field-relevant digital transformation strategies.